Current State and Prospects of Russian Outbound Tourism - KOZLOV, Dmitry Aleksandrovich (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.9.6(30).16, 2019)
The main aim of this paper is to analyze the Russian outbound tourism flow: problems of Russian tourist market, causes and consequences of repeated crisises. According to key findings, Russian tourist market is influenced by several factors. Developed equation of multiple variable regression model indicates that the main factors are wage of Russian’s converted in Euro and gross domestic product per capita. Regression model has great quality parameters and may be used to predict future condition of Russian outbound tourism. Russian Government makes all efforts to reorient own population to domestic tourism cutting off access to the rich world heritage. The decline in real incomes, the lack of regulation of tourist activities, the shortcomings of legislation, the lack of responsibility to customers are led to the decreasing of Russian outbound and domestic tourisms.